Influence of Stochastic Resonance on Manual Dexterity in Children With Developmental Coordination Disorder: A Double-Blind Interventional Study - Nobusako, Satoshi; Osumi, Michihiro; Matsuo, Atsushi; Furukawa, Emi; Maeda, Takaki; Shimada, Sotaro; Nakai, Akio; Morioka, Shu (Frontiers in Neurology, 2021)
Background: There is increasing evidence that the stochastic resonance (SR) phenomenon provided by subthreshold mechanical noise stimulation improves the sensory-motor system. However, the effect of SR on children with developmental coordination disorder (DCD) is unclear. The purpose of this study was to assess whether SR activated by subthreshold vibrotactile noise stimulation of the wrist influences manual dexterity in children with DCD. Methods: A double-blind interventional study was conducted. Participants were 30 children (age: 9.3 ± 1.44 years, range 6–11 years; 27 male, 3 female; 25 right-handed, 5 left-handed) meeting DCD diagnostic criteria in DSM-5. The manual dexterity test was administered the day before SR intervention (baseline-data). SR was elicited using subthreshold vibrotactile noise stimulation at 60% of the vibrotactile threshold measured at the wrist. SR was delivered two times and the manual dexterity test was administered during each SR stimulation block (SR-on condition) and after each SR stimulation block (SR-off), for a total of four measurements. Target outcomes were the component score, the standard score, and the percentile score of the manual dexterity test. Results: The manual dexterity test scores in the SR-on condition were significantly improved compared to scores at the baseline and in the SR-off condition (p < 0.001). Conclusions: The present study showed that subthreshold noise stimulation eliciting SR significantly improved manual dexterity outcomes in children with DCD during stimulation but not after stimulation. Future studies will need to investigate the carry-over effects of SR stimulation.